The critical treatment window of clozapine in treatment-resistant schizophrenia: Secondary analysis of an observational study. (April 2017) - Yoshimura, Bunta; Yada, Yuji; So, Ryuhei; Takaki, Manabu; Yamada, Norihito
Abstract: Previous studies have suggested that a delay in initiating clozapine is one of the predictors of outcomes in treatment-resistant schizophrenia (TRS). However, whether there is a critical treatment window of clozapine in TRS and the duration of that window remain unclear. We conducted a secondary analysis of a previously published observational study using a retrospective chart review of 105 patients with TRS who were treated with clozapine. We included 90 patients who remained on clozapine for at least 3 months. The delay in initiating clozapine was an independent contributor to symptomatic improvement based on treatment with clozapine by multiple linear regression analysis. A receiver operating characteristic curve analysis (area under the curve: 0.78) confirmed 2.8 years was the best predictive cut-off value of delay in initiating clozapine for responses in patients treated with clozapine (sensitivity: 0.66, specificity: 0.84). In patients with a delay in initiating clozapine of ≤2.8 years and a delay in initiating clozapine of >2.8 years, the response rates were 81.6% and 30.8% (risk ratio=2.65; 95% confidence interval, 1.80, 3.63), respectively. Clinicians should reduce the delay in initiating clozapine to less than 3 years to improve symptomatic outcomes in TRS and to prevent clozapine-resistant schizophrenia. Highlights: There is a long delay in initiating clozapine during routine clinical practice. The delay may be an independent predictor of symptomatic outcome. Clinicians should reduce the delay in initiating clozapine to less than 3 years.